Deep Inspiration Breath Hold: Techniques and Advantages for Cardiac Sparing During Breast Cancer Irradiation - Bergom, Carmen; Currey, Adam; Desai, Nina; Tai, An; Strauss, Jonathan B. (Frontiers in Oncology, 2018)
Historically, cardiac toxicity has diminished the benefits of radiation therapy for patients with left-sided breast cancer. Data suggests that there is not a threshold for the deleterious effects from radiation on the heart. Over the last several years, advances in radiation delivery techniques have reduced cardiac morbidity due to treatment. Deep-inspiration breath hold (DIBH) is a technique that takes advantage of a more favorable position of the heart during inspiration to minimize heart doses over a course of radiation therapy. In the accompanying review article, we outline several methods used to deliver treatment with DIBH, quantify the benefits of DIBH treatment, discuss considerations for patient selection, and identify challenges associated with DIBH techniques.